Efficient Polytelluride Anchoring for Ultralong-Life Potassium Storage: Combined Physical Barrier and Chemisorption in Nanogrid-in-Nanofiber - Li, Qinghua; Yu, Dandan; Peng, Jian; Zhang, Wei; Huang, Jianlian; Liang, Zhixin; Wang, Junling; Lin, Zeyu; Xiong, Shiyun; Wang, Jiazhao; Huang, Shaoming (Nano-Micro Letters, 2024)
Metal tellurides (MTes) are highly attractive as promising anodes for high-performance potassium-ion batteries. The capacity attenuation of most reported MTe anodes is attributed to their poor electrical conductivity and large volume variation. The evolution mechanisms, dissolution properties, and corresponding manipulation strategies of intermediates (K-polytellurides, K-pTex) are rarely mentioned. Herein, we propose a novel structural engineering strategy to confine ultrafine CoTe2 nanodots in hierarchical nanogrid-in-nanofiber carbon substrates (CoTe2@NC@NSPCNFs) for smooth immobilization of K-pTex and highly reversible conversion of CoTe2 by manipulating the intense electrochemical reaction process. Various in situ/ex situ techniques and density functional theory calculations have been performed to clarify the formation, transformation, and dissolution of K-pTex (K5Te3 and K2Te), as well as verifying the robust physical barrier and the strong chemisorption of K5Te3 and K2Te on S, N co-doped dual-type carbon substrates. Additionally, the hierarchical nanogrid-in-nanofiber nanostructure increases the chemical anchoring sites for K-pTex, provides sufficient volume buffer space, and constructs highly interconnected conductive microcircuits, further propelling the battery reaction to new heights (3500 cycles at 2.0 A g−1). Furthermore, the full cells further demonstrate the potential for practical applications. This work provides new insights into manipulating K-pTex in the design of ultralong-cycling MTe anodes for advanced PIBs. Highlights: 1 The hierarchical nanogrid-in-nanofiber-structured dual-type carbon-confined CoTe2 nanodots (CoTe2@NC@NSPCNFs) were synthesized via facile templates and an electrospinning approach. 2 Hierarchical nanogrid-in-nanofiber structure effectively suppresses the volume change of CoTe2 and the shuttle of potassium polytelluride (K-pTex) through robust physical restraint and strong chemisorption. 3 CoTe2@NC@NSPCNFs hybrid achieves ultralong lifespan potassium-storage performance over 3500 cycles, and the deep mechanisms underlying the evolution, dissolution, and shuttle of K-pTex have been clearly revealed.